A „kegyetlenül szomorú kötelesség" - A trianoni békediktátum becikkelyezése 1. : 1920. június - 1920. október - Vizi, László Tamás (Közép-Európai Közlemények, 2016)
The peace treaty that was signed by the representatives of the Hungarian government at the Grand Trianon Palace in Versailles on the 4th June 1920, closed the hostilities between the warring parties, and with its 364 articles, it recorded the severe conditions of peace, striking on the defeated Hungary. The peace agreement has not yet become effective with the signing ceremony. The enactment, ratification and sanction of the signed treaty were just ahead. Since the peace treaty was among the international agreements that came in force only after the ratification – and the implementation could also be demanded after the act – the Hungarian party done all to ensure that the ratification take place as late as possible. They wanted to achieve their limited revisionist goals during this period. However, the victorious powers urged the prompt ratification. It was more than a year process from the beginning of the ratification till the peace agreement entered into force which period can be divided into two major clearly separable phases. The first phase lasted from the signing of the peace treaty on 4 June 1920 till 26 October 1920 with its submission to the National Assembly. The second phase includes parliamentary debates and the ratification itself lasting until 26 July 1921, the exchanging of the ratification documents. The size of the subject made it necessary to present the events of the two periods in two separate studies. Thus, the present study describes and analyzes the events of the first period. The essay gives full details of the ratification as an international norm, covering the codification position of Hungary and the Little Entente states and, relating to the victorious powers efforts. The document gives a detailed analyzes of the great powers’s policy which finally forced the Hungarian government to submit the ratification of the Trianon Peace Treaty to the National Assembly.